Remnant cholesterol and atherosclerotic disease in high cardiovascular risk patients: beyond LDL cholesterol and hypolipidemic treatment - Delialis, Dimitrios; Georgiopoulos, Georgios; Aivalioti, Evmorfia; Mavraganis, Georgios; Dimopoulou, Angeliki-Maria; Sianis, Alexandros; Aggelidakis, Lasthenis; Patras, Raphael; Petropoulos, Ioannis; Ioannou, Sofia; Syrigou, Rodanthi; Chatzidou, Sofia; et al. (Hellenic journal of cardiology, 2022)
Background - Remnant cholesterol (RC) is an emerging factor contributing to residual risk for the development of atherosclerotic cardiovascular disease (ASCVD). We aimed to investigate the association of RC with ASCVD in high ASCVD risk patients. - Methods - RC was calculated in 906 participants (178 low/moderate-risk and 728 high-risk) consecutively recruited from a vascular registry. Subclinical carotid atherosclerosis was assessed by B-mode carotid ultrasonography. Maximal carotid wall thickness (maxWT) and carotid atherosclerotic burden (n ≥ 2 atherosclerotic plaques) were set as the vascular outcomes. An independent cohort of 87 consecutively recruited high-risk patients who were followed for their lipid profile for 3 months was also analyzed. - Results - RC was increased in the high-risk group as compared to controls (26 ± 17 vs. 21 ± 11 mg/dl, respectively, p < 0.001). Increased RC levels were independently associated with increased maxWT and carotid atherosclerotic burden (p < 0.05), after adjustment for traditional cardiovascular risk factors (TRF) and ASCVD. RC levels were associated with the presence of flow-limiting ASCVD and coronary artery disease (CAD) (p < 0.05), after adjustment for TRFs. These associations remained significant in those not receiving hypolipidemic treatment and in treated individuals achieving LDL-C<100 mg/dl. In the prospective cohort, there was no significant interaction between change in RC levels and hypolipidemic status, as contrasted to LDL-C levels (p < 0.001). - Conclusion - In a high-risk population, RC was associated with subclinical and clinically overt ASCVD, particularly in patients with the most adverse lipid phenotype (untreated) or in treated patients with a low LDL-related risk profile. These findings support a residual pro-atherosclerotic role of RC in high-risk patients.
Online verfügbar: 4. Juni 2022, Artikelversion: 9. August 2022
Gesehen am 10.09.2024